2020
DOI: 10.11648/j.ajlm.20200504.11
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and Syphilis Sero-prevalence Among Pregnant Women Attending Antenatal Care Center in Rwanda

Abstract: Sexually transmitted infections pause a global challenge. Mostly, human immunodeficiency virus (HIV) and syphilis which are both transmitted sexually, infect a substantial number of people where female are at front line of exposure and high risk. Additionally, pregnant women experience more vulnerability exposing their infants to increased risk of dying from prematurity, low-birth-weight, stillbirth and congenital diseases. Therefore, continued surveillance of this co-infection is of paramount to establish the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
1
Order By: Relevance
“…A comparable result (0.73%) was obtained from Republic of Congo [ 37 ]. While a study in Tanzania reported lower (0.3%) prevalence [ 35 ], another study from Rwanda indicated higher (1.2%) prevalence [ 38 ] of syphilis-HIV co-infection relative to the findings of this study. The difference in prevalence of syphilis-HIV co-infection might be attributed to the variation in level of implementation and integration of STI prevention and control measures in different countries.…”
Section: Discussioncontrasting
confidence: 84%
“…A comparable result (0.73%) was obtained from Republic of Congo [ 37 ]. While a study in Tanzania reported lower (0.3%) prevalence [ 35 ], another study from Rwanda indicated higher (1.2%) prevalence [ 38 ] of syphilis-HIV co-infection relative to the findings of this study. The difference in prevalence of syphilis-HIV co-infection might be attributed to the variation in level of implementation and integration of STI prevention and control measures in different countries.…”
Section: Discussioncontrasting
confidence: 84%